Histopathologic Response to Highly Purified Liquid Silicone Injected Intradermally in Rats' Skin - TÜRKÖZ, HÜSEYİN KEMAL (SPRINGER, 2011)
This study aimed to assess and compare the tissue response to small- and large-volume injections of pure liquid silicone in rats. The study used 25 Sprague-Dawley rats. Two different injection sites were determined for a single rat, and 5000 centistoke liquid silicone was injected subdermally using 0.2-0.3 ml (small volume) and 1 ml (large volume) injections. After the injections, 15 animals were killed at 4 weeks and 10 animals at 10 weeks. Tissue responses were evaluated under a light microscope. At week 4, the numbers of lymphocytes and neutrophils were higher in the small-volume injection group. At week 10, the number of neutrophils decreased, and the numbers of macrophages and foreign body giant cells increased in the small-volume injection group, whereas the intensity and type of infiltrate in the large-volume injection group did not change significantly. The thickness of the fibrous capsule was greater in large-volume injection group at weeks 4 and 10. The thickness of the fibrous capsule did not change significantly in either group through time. Purified high-density liquid injectable silicone causes a low-grade and well-tolerated inflammatory response during the long term and can be used when given as small-volume injections.
Keywords: Complication; Granuloma; Histopathology; Liquid silicone; Nodule; Rat; HOST RESPONSE; FLUID; AUGMENTATION; HISTORY